Exploring Dickens’ Stylistics : Pedagogical Strategies for Enhancing Literature Teaching and Learning - Fahri, Fahri; Zuhri, Fauris; Subandiyah, Heny; Abida, Fithriyah Inda Nur; Sumarniningsih, Sumarniningsih (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study explores the impact of incorporating the stylistic method and diverse pedagogical approaches on students' understanding and appreciation of literary works, specifically focusing on the works of Charles Dickens. This research used a mixed-methods approach, combining qualitative methods such as observation, surveys, and text analysis with quantitative methods involving statistical analysis. The quasi-experimental design selected undergraduate students purposively based on their literary background, with Charles Dickens' notable works serving as key resources. Pre and post-tests are administered to experimental and control groups to measure the impact of language style instruction. Results indicate that the experimental group, exposed to language style teaching, outperforms the control group in post-teaching comprehension tests. Studies show that teaching students about language styles helps them unlock the meaning of literature. Questionnaire data demonstrate high student satisfaction, increased confidence, improved critical thinking, and enhanced analytical abilities. The adaptability of Dickens's novels to various learning styles contributes to a more inclusive learning environment.